(untitled) (Research, Society and Development, 2022)
Over the centuries, the human race has exhibited a history of health emergencies, epidemics that were marked by high rates of infection and mortality. The most recent, severe acute respiratory syndrome (SARS-CoV-2), better known as COVID-19, the main forms of prevention recommended by the Ministry of Health are directly associated with hands, such as avoiding handshakes and hugs, direct contact with eyes, nose and mouth, and, above all, wash it frequently with soap and water or sanitize with 70% alcohol gel. Gel alcohol has the function of denaturing proteins, so alcoholic solutions containing an alcohol percentage of 70% are very effective, with smaller or larger concentrations being less potent. The objective of this study is to analyze the physical-chemical quality of gel alcohol available in commercial establishments in the municipality of Vitória da Conquista - BA during the COVID-19 pandemic period. This is an exploratory, cross-sectional and quantitative study carried out from the collection of alcohol gel samples in five commercial establishments. Evaluating the physical-chemical characteristic; organoleptic properties, pH, resistance to centrifugation, verification of alcohol content and density. Thus, it was observed that none of the samples fit the established parameters, such as more acidic pH, alcohol content above the ideal, density outside the standard, indicating nonconformities that affect the quality and action of the product. Therefore, it is concluded that, only a drafting of laws is not enough to guarantee the quality and safety of the product, it is necessary a more rigorous inspection and the elaboration of more qualified laws.